2021
DOI: 10.1002/jbm4.10571
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Obesity, Ovariectomy, and Greenshell Mussel Supplementation on Bone Mineral Density in Rats

Abstract: Obesity is considered to impair long-term health by disturbing multiple physiological functions. However, it remains a controversial issue as to whether obesity has beneficial or detrimental effects on bone health in postmenopausal women. The aims of this study were to investigate the relationships between obesity and bone mineral density (BMD) under conditions of ovarian hormone deficiency in an animal model and to evaluate the potential health benefits of Greenshell mussel (GSM) on bone health. A total of 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…As such it appeared that having a high fat mass could impose a negative effect on bone mass that is different from that of normal weight-bearing. Other research has revealed that even though rats appeared to show beneficial improvements in bone mineral density in response to the presence of excess body mass in an osteoporosis model, 15 Turcotte et al, 16 confirmed obesity does appear to induce apparent beneficial increases in the bone mineral density of overweight human subjects, along with an enhancement of their bone micro architecture and bone strength. On the other hand, Lopez-Gomez et al, 17 found postmenopausal women who were deemed obese tended to show lower levels of bone formation markers than those who were deemed to be of a healthy weight.…”
Section: Resultsmentioning
confidence: 97%
“…As such it appeared that having a high fat mass could impose a negative effect on bone mass that is different from that of normal weight-bearing. Other research has revealed that even though rats appeared to show beneficial improvements in bone mineral density in response to the presence of excess body mass in an osteoporosis model, 15 Turcotte et al, 16 confirmed obesity does appear to induce apparent beneficial increases in the bone mineral density of overweight human subjects, along with an enhancement of their bone micro architecture and bone strength. On the other hand, Lopez-Gomez et al, 17 found postmenopausal women who were deemed obese tended to show lower levels of bone formation markers than those who were deemed to be of a healthy weight.…”
Section: Resultsmentioning
confidence: 97%
“…This model has been frequently used in obesity research as the convenience of the protocol and representing the public health problem. The surgical model using ovariectomy in female subjects can mimic the menopause condition in women as estrogen loss induces increased food consumption at the transitional period (Siriarchavatana et al, 2022) and worsens metabolic and lipid profiles (Siriarchavatana et al, 2020;Abshirini et al, 2021). Boonyapakorn et al (2019) demonstrated that lacks of testosterone in castrated dogs resulted in significant weight gain due to the reduction of physical activities but this manipulation did not affect metabolic profiles or cardiac function.…”
Section: Discussionmentioning
confidence: 99%